Effect of gestational diabetes mellitus on the expression of amelogenin in rat offspring tooth germ - Nurdiana Dewi; Ahmad Syaify; Ivan Arie Wahyudi (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2013)
Background: Amelogenin is a major protein constituent of the developing enamel matrix that is critical for enamel formation. Mutations of amelogenin cause hypoplastic enamel phenotypes. Previous research found that infant of diabetic mother has higher risk for having enamel hypoplasia. Purpose: The aim of this study was to determine the effect of gestational diabetes mellitus on the expression of amelogenin in Wistar rats offspring tooth germ. Methods: Sixteen female Wistar rats, aged 2.5-3 months, body weight 150-200 g were used in this study, Wistar rats were mated and divided into two groups and treated on day 0 of pregnancy. Group A was DM group, consisting of 8 rats, induced by streptozotocin (STZ) injection 40 mg/kg BW. Group B was control group, consisting of 8 rats received citrate buffer injection. Thirty-two rat pups were decapitated on day 5. Immunohistochemical procedures were performed on molar tooth germ of the mandibular rat pups using antibody anti-AMELX to determine the expression of amelogenin. Examination carried out on the images using ImageJ software. All data were then statistically analyzed by Mann Whitney test. Results: There was no significant difference in the expression of amelogenin in the DM group and control group (p>0.05). Conclusion: Gestational diabetes mellitus did not affect the expression of amelogenin in rat offspring tooth germ. Further study is needed to examine the pattern of amelogenin expression with measurement of glucose levels of rat pups.Latar belakang: Amelogenin merupakan protein terbanyak pada matriks email yang berperan penting dalam pembentukan email. Mutasi pada amelogenin dapat menyebabkan email menjadi hipoplastik. Penelitian sebelumnya menunjukkan bahwa anak yang dilahirkan oleh ibu pengidap diabetes memiliki resiko lebih tinggi untuk mengalami hipoplasia email. Tujuan: Penelitian ini bertujuan untuk meneliti pengaruh diabetes mellitus gestasional terhadap ekspresi amelogenin pada benih gigi anak tikus Wistar. Metode: Enam belas ekor tikus Wistar betina, umur 2,5-3 bulan, berat badan 150-200 g digunakan dalam penelitian ini, dikawinkan kemudian dibagi menjadi dua kelompok dan diberi perlakuan pada kehamilan hari ke-0. Kelompok A merupakan kelompok diabetes mellitus, terdiri atas 8 ekor tikus diberi perlakuan diabetes mellitus dengan injeksi streptozotocin (STZ) 40 mg/kg BB. Kelompok B merupakan kelompok kontrol, terdiri atas 8 ekor tikus diberi injeksi buffer sitrat. Tiga puluh dua anak tikus yang lahir didekapitasi pada hari ke- 5. Dilakukan prosedur imunohistokimia pada benih gigi molar rahang bawah anak tikus menggunakan antibodi anti-AMELX untuk mengetahui ekspresi amelogenin. Pemeriksaan dilakukan pada hasil foto menggunakan software ImageJ. Hasil kemudian dianalisa menggunakan uji Mann Whitney. Hasil: Tidak terdapat perbedaan yang bemakna pada ekspresi amelogenin kelompok kontrol dan kelompok diabetes mellitus (p>0,05). Simpulan: Diabetes mellitus gestasional tidak mempengaruhi ekspresi amelogenin pada benih gigi anak tikus. Diperlukan penelitian lebih lanjut untuk mengetahui pola ekspresi amelogenin dengan pengukuran kadar glukosa darah anak tikus.